Corrections to “A Method for Detecting Small Slow Targets on Sea Surface Based on FC-MCNN” - Qing Sun; Jing Zhao; Chunling Xue; Xueting Yang (IEEE Access)
Presents corrections to the paper, A Method for Detecting Small Slow Targets on Sea Surface Based on FC-MCNN.